Pengembangan Modul Pembelajaran Biologi Berbasis Keterampilan Proses Sains pada Materi Struktur dan Jaringan Tubuh Hewan Kelas XI SMA/MA - Baharsyah, Vivi Salvia; Rachmawaty, Rachmawaty; Nurhayati, B, Nurhayati, B (Biology Teaching and Learning, 2019)
Abstract. The type of research is research and development (R & D). The purpose of this research was to develop of Biological learning module based on Scale Process Skills (SPS) on material structure and function of tissue animal that is valid and practical for Senior High School students. The development procedure used in this study is the ADDIE model which consists of five stages namely Analysis, Design, Development, Implementation, and Evaluation. Data collection was done through the validation process of the learning module and questionnaire responses of students and teachers to the learning module. The collected data was analyzed using quantitative descriptive analysis. The results of the study indicate that SPS of based biology learning modules were "valid" and "very practical". Valid because the SPS of based biology learning module developed has fulfilled the validity criteria in the valid category. The learning module is said to be very practical because students and teachers respond very positively to the learning module.Keywords: biology module, science process skills, structure and function ofÂ  animals tissue